Geomorphological and environmental changes of South Attica coastal zone. - Vassilopoulos, A.; Evelpidou, N.; Komianou, A. (1st Conference of the European Federation of Marine Science and Technology Societes (EFMS), 2002)
In this study we examined the geomorphological and environmental characteristics of south Attika coastal zone (from Voula area to Lagonisi), a region in which man-made influence is very intense. This paper includes the detection of features of the coastal zone, that are in danger of alteration, because of their exposure to human intervention; it results to the study of the above characteristics and their mapping, with a purpose of using the final thematic maps in future study of the area, after the oncoming changes, because of the Olympic games of 2004. For this purpose we developed a database with geographical, geological, geomorphological and environmental characteristics in GIS and we created the corresponding thematic maps. Data collection took place through photointerpretation of corresponding aerial photos and fieldwork of the coastal zone (from inland and offshore) with the use of GPS.